An Analysis on Understanding Localization Issues in Translating English Comics “Robber X Lover” to Indonesian - Clarissa Arief; Wulandari Santoso (CV. Creative Tugu Pena, 2025)
Comic translation is more than a linguistic exercise; it involves a complex process of localization to ensure that the intended meaning, humor, and cultural nuances of the source text are effectively conveyed in the target language. This study analyzes the challenges of non-equivalence in translating English comics into Indonesian, using a fan translation of Robber x Lover by Pengki as a case study. The research focuses on identifying difficult-to-translate words, phrases, and sentences from the original text and evaluates the translation using Prof. Nababan’s Translation Quality Assessment (TQA) model. Baker’s (2011) theory of non-equivalence and corresponding strategies is employed as the theoretical framework. The study found nine instances of problematic translation, primarily caused by the lack of localized concepts. These were resolved using the paraphrasing strategy, which was consistently effective during both the initial translation and the revision process. The findings highlight that paraphrasing plays a crucial role in overcoming non-equivalence issues and enhancing localization in comic translation.: This study contributes to the field of translation studies by providing empirical evidence on the effectiveness of paraphrasing in addressing non-equivalence and supporting localization in comic translation. It underscores the importance of combining linguistic strategies with cultural adaptation to achieve high-quality translations. The findings offer practical insights for translators, educators, and researchers, and suggest that future studies should explore diverse comic genres to further validate the applicability of these strategies across broader contexts.